Hsf1 and Hsf2 in normal, healthy human tissues: Immunohistochemistry provokes new questions - Mayer, Matthias P. (Cell stress & chaperones, 2024)
The heat shock transcription factors heat shock transcription factor 1 and Hsf2 have been studied for many years, mainly in the context of stress response and in malignant cells. Their physiological function in nonmalignant human cells under nonstress conditions is still largely unknown. To approach this important issue, Joutsen et al. present immunohistochemical staining data on Hsf1 and Hsf2 in 80 nonpathological human tissue samples. The wealth of these data elicits many interesting questions that will spur many future research projects.
Online verfügbar 18 April 2024, Version des Artikels 27 April 2024
Gesehen am 08.11.2024